LINGUOMENTAL CATEGORY OF RELEVANCE AND LEXICAL MEANS OF ITS REPRESENTATION - Черникова, Наталия Владимировна; Рассказов, Николай Юрьевич; Орлова, Ирина Александровна (Bulletin of the Chuvash State Pedagogical University named after I Y Yakovlev, 2021)
В статье доказана правомерность выделения лингвоментальных категорий как совокупностей концептов и вербализующих их знаков (языковых единиц), которые характеризуются однородностью на основе общности определенного признака, фиксирующего результаты когнитивной деятельности человека. Обосновано выделение лингвоментальной категории актуальности, аккумулирующей социально значимые на конкретном историческом этапе концепты (ментальные знаки), которые репрезентированы языковыми единицами, образующими активный словарь носителей языка. Сформулировано определение аткуалемы - ментального знака, объективирующего категорию актуальности; охарактеризованы ее признаки, в числе которых хронологическая детерминированность, социокультурная маркированность, смысловая разносторонность, динамичность. Рассмотрен состав актуальной лексики современного русского языка, включающий лексические и семантические неологизмы, внешние и внутренние заимствования, актуализированную и номинативно переориентированную лексику. Установлено, что состав корпуса актуалем и репрезентирующих их языковых знаков детерминирован внешними (политическими, экономическими, социокультурными) факторами. Актуальность исследования обусловлена отсутствием системного изучения динамических процессов актуализации на русском языковом материале. The article proves the legitimacy of identifying linguomental categories as sets of concepts and their verbalizing signs (linguistic units). Concepts and their verbalizing signs are characterized by homogeneity based on the commonality of a certain feature. Certain feature fixes the results of human cognitive activity. The allocation of the linguomental category of relevance is substantiated. The linguomental category of relevance accumulates concepts (mental signs) that are socially significant at a particular historical stage, which are represented by linguistic units that form an active layer of native speakers. The definition of actualema is formulated. Actualema is a mental sign that objectifies the category of relevance; its features are characterized, including chronological determinism, sociocultural marking, semantic versatility, dynamism. The composition of the actual vocabulary of the modern Russian language is considered. The composition of the actual vocabulary includes lexical and semantic neologisms, external and internal borrowings, updated and nominatively reoriented vocabulary. It has been established that the composition of the corpus of the actual and the linguistic signs representing them is determined by external (political, economic, socio-cultural) factors. The relevance of the research is due to the lack of a systematic study of the dynamic processes of actualization in Russian language material.